Polypyrrole-based nanocomposites doped with both salicylate/molybdate and graphene oxide for enhanced corrosion resistance on low-carbon steel - Ha Manh Hung; Tran Minh Thi; Le Van Khoe; Le Minh Duc; Hoang Thi Tuyet Lan; Lai Thi Hoan; Vu Thi Xuan; Nguyen Thi Bich Viet; Ngo Xuan Luong; Nguyen Thuy Chinh; Thai Hoang; Vu Thi Hương; et al. (Designed Monomers and Polymers, 2023)
In this work, polypyrrole-based nanocomposites doped with graphene oxide, molybdate, and salicylate (PPy/GO/Mo/Sal) were synthesized via in situ electrochemical polymerization to enhance the anti-corrosion protection performance of polymer coatings. The morphology and structures of the coatings were characterized by SEM, EDX, FTIR, Raman spectroscopy, and XRD. The protection abilities of coatings against corrosion were investigated in 0.1 M NaCl solution with EIS potentiodynamic polarization, salt spray test, and open-circuit potential (OCP) measurements. The results showed that with the presence of both molybdate/salicylate and GO in the PPy matrix, the nanocomposite coating exhibited an excellent protection ability against corrosion for low-carbon steel, better than that with only GO as filler. Compared to the nanocomposites doped with only salicylate or salicylate/GO, the one doped with both molybdate/salicylate and GO exhibited the longest protection plateau (ca. 100 h) on the OCP-time curves with some fluctuation points known as the self-healing action of molybdate dopant. It also resulted in a decrease in the corrosion current (Tafel plots), a higher impedance (Bode plot), and a better protection performance in salt spray tests. In this case, the anti-corrosion ability of the coatings was provided through a barrier and self-healing mechanism.